CmFSI8/CmOFP13 encoding an OVATE family protein controls fruit shape in melon. (24th November 2021) - Ma, Jian; Li, Congcong; Zong, Mei; Qiu, Yanhong; Liu, Yuemin; Huang, Yating; Xie, Yuli; Zhang, Huijun; Wang, Jianshe
Abstract: Fruit shape is an important quality and yield trait in melon ( Cucumis melo ). Although some quantitative trait loci for fruit shape have been reported in in this species, the genes responsible and the underlying mechanisms remain poorly understood. Here, we identified and characterized a gene controlling fruit shape from two melon inbred lines, B8 with long-horn fruit and HP22 with flat-round fruit. Genetic analysis suggested that the shape was controlled by a single and incompletely dominant locus, which we designate as CmFSI8 / CmOFP13 . This gene was finely mapped to a 53.7-kb interval on chromosome 8 based on bulked-segregant analysis sequencing and map-based cloning strategies. CmFSI8 / CmOFP13 encodes an OVATE family protein (OFP) and is orthologous to AtOFP1 and SlOFP20 . The transcription level of CmFSI8 / CmOFP13 in the ovary of HP22 was significantly higher than that in B8, and sequence analysis showed that a 12.5-kb genomic variation with a retrotransposon insertion identified in the promoter was responsible for elevating the expression, and this ultimately caused the differences in fruit shape. Ectopic overexpression of CmFSI8 / CmOFP13 in Arabidopsis led to multiple phenotypic changes, including kidney-shaped leaves and shortened siliques. Taken together, our results demonstrate the involvement of an OFP in regulating fruit shape in melon, and our improved understanding of the molecular mechanisms will enable us to better manipulate fruit shape in breeding. Abstract : CmFSI8 / CmOFP13 encodes an OVATE family protein and its expression in melon ovaries is associated with development of fruits with a flat-round shape.